Allelopathic potential of Cynodon dactylon (L.) Pers. on the germination and growth of durum wheat (Triticum durum Desf.) - Melakhessou Z.; Demnati F.; Demes M.R. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
In this work, we investaged laboratory tests for the evaluation of the allelopathic effect of aqueous extracts of Cynodon dactylon L. on the germination and growth of three variety (variety MBB, GTA DUR and VITRON). In general, an inhibitory effect is observed on all studied parameters namely germination, radicle length, coleoptiles length as well as the production of dry matter. This effect occurs at the lowest concentration (10 g/l) and the reduction rate increases with the increase of the concentration of the extracts (20 g/l, 30 g / l and 40 g/l).
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)